The place in the novels of Nawzat Shamdin - Nawaf, Maysaloon Nouri (Al-Adab Journal, 2022)
The city of Mosul represents The Place From which the Characters of the novels of the novelist Nawzat Shamdin Originated the Identity of the Place was the Topic that the novelist dealt with as he tried to give the most accurate details about the blades, Levying on the description and his extensive me moray of his city. He was able to Paint with his own words the difficult condition that Mosul ears Subjected to over time.